a^(n + m) = a^n * a^n
a^ log(a) b = b
5^(3 + log(5) 15) = 5^3 * 5^log(5) 15 = 125 * 15 = 1875
Ответ:
1875
5^(3 + log₅15) = 5³ * 5^(log₅15) = 125 * 15 = 1875
Объяснение:
5^(3 + log₅15) = 5³ * 5^(log₅15) по формуле a^(b + c) = a^b + a^c
5^(log₅15) = 15 по формуле a^(logₙb) = b
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
a^(n + m) = a^n * a^n
a^ log(a) b = b
5^(3 + log(5) 15) = 5^3 * 5^log(5) 15 = 125 * 15 = 1875
Verified answer
Ответ:
1875
5^(3 + log₅15) = 5³ * 5^(log₅15) = 125 * 15 = 1875
Объяснение:
5^(3 + log₅15) = 5³ * 5^(log₅15) по формуле a^(b + c) = a^b + a^c
5^(log₅15) = 15 по формуле a^(logₙb) = b